Biomarkers of exposure to metal dust in exhaled breath condensate: methodology optimization - Félix, P. M. (2014)
In occupational assessments where workers are exposed to metal dust, the liquid condensate of exhaled breath (EBC) may provide unique indication of pulmonary exposure. The main goal of this study was to demonstrate the quality of EBC to biological monitoring of human exposure. A pilot study was performed in a group of metal dust–exposed workers and a group of nonexposed individuals working in offices. Only metal dust–exposed workers were followed along the working week to determine the best time of collection. Metal analyses were performed with inductively coupled plasma mass spectrometry (ICP-MS). Analytical methodology was tested using an EBC sample pool for several occupationally exposed metals: potassium, chromium, manganese, copper, zinc, strontium, cadmium, antimony, and lead. Metal contents in EBC of exposed workers were higher than controls at the beginning of the shift and remained augmented throughout the working week. The results obtained support the establishment of EBC as an indicator of pulmonary exposure to metals.